THE EFFECT OF USING SURFACTAN TO REMOVE FATTY SPEW STAINS ON GOLF GLOVE LEATHER - Selvyan Ellenika Putri; Elis Nurbalia; Emiliana Anggriyani (Politek ATK Yogyakarta Press, 2022)
Fatty spew is a stain found in leather that has been tanned with chrome. The appearance of fatty spew is caused by the content of free fatty acids which is too high. The purpose of this experiment was to determine the effect of using surfactant as a washing agent in removing fatty spew stains on golf glove leather. The raw materials used were 2 sheets of chrome tanned crust measuring 11 sqft with a weight of 206 g and a shaving thickness of 0.4-0.5 mm. The process carried out is by washing using a washing agent in the form of a surfactant as much as 0.6% of the weight of the skin. Washing was carried out for 30 minutes using a process drum. The results of the washing showed that fatty spew stains on the crust skin obtained maximum results after washing there was a slight change in the surface of the skin that felt a little rough, so additional polishing treatment was needed. The conclusion obtained is that the use of surfactants obtains maximum results in removing fatty spew stains on the crust skin.